The Mediating Role of E-WOM in the Effect of Viral Marketing on Purchase Intention (A Study on Bakmi Akiu in Denpasar City) - I.G. Ratu Gita Susila; Ni Made Rastini (PT FORMOSA CENDEKIA GLOBAL, 2025)
One of the technical innovations that has revolutionized how companies function and engage with their customers is digital marketing. One company that uses digital marketing on social media sites like Instagram and TikTok is Bakmi Akiu. According to an interview with the company's CEO, Bakmi Akiu's viral marketing efforts on social media did not significantly boost their customer base. A survey method was used to gather data, and 120 respondents were given online questionnaires. Path analysis in conjunction with the Sobel test was the analysis method employed. The analysis's findings demonstrated that viral marketing significantly and favorably influences purchase intention, that viral marketing significantly and favorably influences E-WOM, that E-WOM significantly and favorably influences purchase intention, and that E-WOM can mediate the impact of viral marketing on purchase intention. The research's theoretical implications include adding to the body of knowledge regarding the efficacy of viral marketing tactics and making a substantial theoretical contribution to the field of digital marketing, especially in relation to consumer behavior theory and the Theory of Planned Behavior. The research's practical implications indicate that in order to maximize the results of viral marketing initiatives and promote the propagation of positive E-WOM, business actors—Bakmi Akiu in particular—should continue to produce interactive and participatory viral content.